Improving Students’ Intensive Reading Ability by Using Survey-Question-Read-Review-Recite-Reflect Method - Ryu Chun Moon; Sang Hee Kwan (Journal of English Language Teaching and Literature)
The current study is a classroom action research with the objective of analyzing the improvement of students’ intensive reading ability using Survey-Question-Read-Review-Recite-Reflect (SQ4R) method. This research was conducted at Ryulgok Secondary School, Pyongyang, by involving 32 the 3rd grade students as the research participants. Data collection techniques were interviews, observation, documentation, and tests. The data analysis method used in this study was divided into qualitative data analysis and quantitative data analysis. The results of the first cycle of the research showed that 58.4% of students were active, it meant that it was still less than the target 75% of the results of intensive reading, because only 53% of students achieved a score of 70 and above for reading ability. In the second cycle, it shows that 85% of students actively participated in learning and the percentage of students was 87% of the target 75% of students got a score of 70 and above for reading ability. This indicated that there was an increase in learning outcomes (reading ability) as a result of an increase in the learning process after using the SQ4R method.